Peranan Sistem Informasi Akuntansi dan Tantangan Profesi Akuntan di Era Revolusi Industri 4.0 (Sebuah Studi Fenomenologi) - Cahyadi, Iwan Fahri (AKTSAR: Jurnal Akuntansi Syariah, 2019)
In the last few years appeared a variety of breakthrough technology that generates new values in human life through a form of artificial intelligence, data, internet of things (IoT). Business circles call the third it as the core of the industrial revolution 4.0. These conditions have an impact on the role of the human being, particularly the challenges of the profession of accountants who will be replaced by the role of the robot.  The purpose of this research is to provide a solution so that the role of the accountants still exist in the era of the industrial revolution 4.0. As for qualitative research methods via the fenomenalogi approach i.e. we allow qualitative researchers implement and apply subjective abilities and exploratory process in interpersonalnya.  Results of the study so that the accountant still exist in the era of the industrial revolution 4.0 then the accountant to start learning programming and algorithms to be able to adapt to change, if you don't use the technology, then the role of the accountant will be replaced by robots.